THE CONCEPT OF CULTURAL RENAISSANCE: AN ANALYSIS OF IDEOLOGY IN DINKAR'S 'SANSKRITI KE CHAR ADHYAY' - Kumar, Priyanshu (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Ramdhari Singh 'Dinkar's' work 'Sanskriti Ke Char Adhyay' is a living example of the concept of Indian cultural renaissance. This book deeply analyzes the tolerance, coordination, and various stages of development of Indian culture. In this work, Dinkar did not limit cultural renaissance to the preservation of traditions, but presented it as a process of making traditions relevant in the modern context. Through the four stages of Indian culture—primitive, Vedic, Buddhist, and modern—he showed that Indian society has maintained its uniqueness while assimilating external influences from time to time. In this paper, the concept of cultural renaissance is explained in the context of Dinkar's ideology. Tolerance, balance between tradition and modernity, and his approach to nationalism are the main focuses of this research. This research shows that 'Sanskriti Ke Char Adhyay' is not just a mirror of the past; It is an effective means of providing direction to Indian society for the present and future. This vision of Dinkar is still very relevant in solving problems like cultural degradation, inequality, and intolerance.